2010
DOI: 10.1002/ar.21192
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Consumption Affects Gastrointestinal Motility and Reduces the Proportion of Neuronal NOS‐Immunoreactive Myenteric Neurons in the Murine Jejunum

Abstract: Alcohol consumption interferes with gastrointestinal transit causing symptoms in alcoholic patients. Nitric oxide (NO), synthesized by neuronal nitric oxide synthase (nNOS) plays an important role in the control of gastrointestinal motility. Our aim was to investigate whether chronic alcohol intake in a murine model induces gastrointestinal motility disturbances and affects the nitrergic myenteric neurons in the stomach and jejunum. Gastric emptying, small intestinal transit and geometric centre were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
(54 reference statements)
2
38
1
Order By: Relevance
“…Alcohol decreases gastric motility in mice. 13 In the small intestine, alcohol decreases the impedance wave motility (muscles that retain food for further digestion) but does not affect the propulsive wave motility (movements that propel food within the intestine) contributing to diarrhea seen in individuals who chronically consume alcohol. 14,15 Alcohol has also been shown to increase intestinal permeability in both animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol decreases gastric motility in mice. 13 In the small intestine, alcohol decreases the impedance wave motility (muscles that retain food for further digestion) but does not affect the propulsive wave motility (movements that propel food within the intestine) contributing to diarrhea seen in individuals who chronically consume alcohol. 14,15 Alcohol has also been shown to increase intestinal permeability in both animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports have described the plastic remodeling of the nitrergic neurons during development [55,58,59] , aging [60] and pathological conditions [22,61] . Several studies have suggested that nitrergic myenteric neurons are especially susceptible to the development of neuropathy in digestive tract diseases, like diabetes [22,[62][63][64][65] , chronic ethanol consumption [66][67][68] and inflammation [69] .…”
Section: Nitrergic Neuronsmentioning
confidence: 99%
“…Chronic intake of alcohol severely affects organs of the body by altering signaling pathways and the function of various cell types. In the gastrointestinal (GI) tract of man 1–3 and experimental animals, 4–6 chronic alcohol consumption (CAC) prominently disturbs normal intestinal motor function leading to motility disturbances 7 . There is some evidence that these motor disturbances are caused by an effect of ethanol on the nitric oxide (NO) system of relaxation in the gut 6,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the gastrointestinal (GI) tract of man 1–3 and experimental animals, 4–6 chronic alcohol consumption (CAC) prominently disturbs normal intestinal motor function leading to motility disturbances 7 . There is some evidence that these motor disturbances are caused by an effect of ethanol on the nitric oxide (NO) system of relaxation in the gut 6,8,9 . In the GI tract, NO produced by enteric neurons is involved in the regulation of motility, secretion and blood flow 10–12 .…”
Section: Introductionmentioning
confidence: 99%